Laju enkapsulasi parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) oleh kutu putih singkong Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) - Evie Adriani; Aunu Rauf; Pudjianto Pudjianto (Jurnal Entomologi Indonesia, 2016)
Parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced into Indonesia in early 2014 to control the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). The objective of study was to determine encapsulation rate of parasitoid A. lopezi by various host instars of P. manihoti. Observation of encapsulation rate was made  by exposing a single mated female of parasitoid on mealybug nymph-1, -2, -3, and adult in a plastic cage for 24 h. Mealybugs then were dissected and number of parasitoid eggs laid and those encapsulated were counted. Study revealed that rate of aggregate encapsulation was highest (8.4%) by adults, followed by nymph-3 (5.8%), nymph-2 (3.1%), and nymph-1 (1.1%). Rate of effective encapsulation by adults was 2.0%, whereas by nymphs about  1.0%. The low rate of encapsulation is believed not to reduce the effectiveness of parasitoid A. lopezi in the biological control of cassava mealybug P. manihoti in Indonesia.